1994
DOI: 10.1515/znb-1994-1107
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of Isocyanides into the Palladium-Carbon Bond of Cyclopalladated Complexes

Abstract: M onodentate, Semicarbazone, Thiosem icarbazone, But-2-yne, Tungsten(II) Reaction of [W I(C O )(N C M e)(dppm )(772 -M eC2M e)][BF4] {dppm = Ph2 P(C H 2 )PPh2} with an equim olar quantity of L {L = R R 'C N N H C O N H 2 (R = R ' = Me; R = H, R ' = Ph)} or L {L = R R 'C N N H C S N H 2 (R = R ' = Me, Et; R = Me, R ' = E t, Pr", Bu', Ph; R = H, R ' = Ph)} gives the m onodentately coordinated sem icarbazone or thiosem icarbazone products [W I(CO)L(dppm)(?7 2 -M eC2M e)][BF4] (1 -9 ) . 13C N M R spectroscopy sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 0 publications
5
29
0
1
Order By: Relevance
“…It appears that the syn-anti ratio of product is affected by donor atoms present in the pincer arms, which also influence diastereoselectivity. The mechanism for the present catalytic reaction may be at variance with those in which donor atoms in the arms of pincer 94,[154][155][156] are other than Se.…”
Section: Catalytic Aldol Type Of Reactions 94mentioning
confidence: 92%
“…It appears that the syn-anti ratio of product is affected by donor atoms present in the pincer arms, which also influence diastereoselectivity. The mechanism for the present catalytic reaction may be at variance with those in which donor atoms in the arms of pincer 94,[154][155][156] are other than Se.…”
Section: Catalytic Aldol Type Of Reactions 94mentioning
confidence: 92%
“…27 As suggested in the case of compound 5, we cannot rule out for 14a,b an incipient penta-coordination resulting from a weak interaction between the dimethylamino group and Pd, even in solution. This hypothesis is moreover supported by a variable-temperature 31 P{ 1 H} NMR study on 14b. The doublet resonance at d 28.8 for the Pd-bound phosphorus, which is well resolved at ambient temperature, broadens upon progressive cooling and collapses finally at −50 • C to a hump, whereas the resonance of the Fe-bound phosphorus nucleus remains unaffected.…”
Section: Migratory Insertion Reactions Of Organic Isocyanidesmentioning
confidence: 67%
“…From the position of the two doublets at d 60.2 and 28.1 it can be concluded that an increasing high-field shift correlates with an increasing number of inserted isocyanide units within the series 16-18. 38 After addition of a fourth equivalent of o-anisylNC, immediate recording of the IR and 31 The outcome of the insertion reactions appears to depend from the electronic properties of the isocyanide reagent. After addition of two equivalents of the more nucleophilic (and more basic) tert-butyl isocyanide to a solution of [(OC) 3 -Fe{l-Si(OMe) 2 (OMe)}(l-dppm)PdMe], the anticipated bis-(insertion) product was not formed even after 1 h reaction time, but instead the bright yellow complex [(OC) 3 {(MeO) 3 Si}-Fe(l-dppm)Pd{C(=NBu t )Me}(CNBu t )] (21) was isolated in good yield.…”
Section: {C(=n-o-anisyl)c(=n-o-anisyl)me}] (17) and The Tris(insertio...mentioning
confidence: 99%
“…Our studies indicate that using electronsupplying substituents, such as sulfur, nitrogen and selenium instead of phosphorus leads to an increase of the amount of the anti product (Table 1). Previous studies indicate that PCP complexes and pincer complexes [50,54] with sulfur or nitrogen atoms in the side arms (such as 1f and 1g) probably react by different mechanisms in aldol reactions. In addition, the difference in the geometric flexibility [55] of complexes 1a-g may also influence the stereochemical outcome of the cyclization reactions.…”
Section: X-ray Structure Of 6amentioning
confidence: 99%